Sensitivity analysis of a type-3 DFAG wind turbine's dynamics with pitch control - Eisa, Sameh A.; Wedeward, Kevin; Stone, William (2016 IEEE Green Energy and Systems Conference (IGSEC), 2016)
In this paper, the model of a type-3 DFAG/DFIG wind turbine generator is considered at higher wind speeds with the pitch control activated. The main blocks of the model taken from the literature are described and translated into a system of differential equations with algebraic constraints. Eigenvalues and steady states of the model are presented with the main focus being the sensitivity analysis of state variables and eigenvalues to the parameters, and how the parameters affect the steady states. Results for sensitivities to a single parameter and two parameters are provided along with a simulation of the dynamics for time-varying wind speed.